2021
DOI: 10.3390/antibiotics10020198
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Coagulase-Negative Staphylococci Isolated from Bloodstream in the uMgungundlovu District of KwaZulu-Natal Province in South Africa: Emerging Pathogens

Abstract: Coagulase-negative staphylococci (CoNS) are increasingly associated with nosocomial infections, especially among the immunocompromised and those with invasive medical devices, posing a significant concern. We report on clinical multidrug-resistant CoNS from the uMgungundlovu District, KwaZulu-Natal Province, South Africa, as emerging pathogens. One hundred and thirty presumptive CoNS were obtained from blood cultures. Culture, biochemical tests, and the Staphaurex™ Latex Agglutination Test were used for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 23 publications
(45 reference statements)
10
22
2
Order By: Relevance
“…The increasing trend of antibiotic resistance of CoNS to various agents has been documented in multiple reports. This is significant, as not only can CoNS develop antibiotic resistance easily, but it can also transfer the developed resistance genes to other microorganisms [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trend of antibiotic resistance of CoNS to various agents has been documented in multiple reports. This is significant, as not only can CoNS develop antibiotic resistance easily, but it can also transfer the developed resistance genes to other microorganisms [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen MRSE isolates, selected as a subsample from a previous study ( Asante et al, 2021 ) based on their resistance profiles, were subjected to whole-genome sequencing (WGS). Briefly, an initial 89 suspected CoNS isolates were collected from blood cultures sourced from hospitals within the uMgungundlovu District in the KwaZulu-Natal Province.…”
Section: Methodsmentioning
confidence: 99%
“…CoNS can colonize specific body parts and cause specific infections; for example, S. haemolyticus is involved in native valve endocarditis and S. saprophyticus is responsible for up to 10% of urinary tract infections in women [7]. In addition, numerous studies have reported an increase in antimicrobial resistance in CoNS, which limits the therapeutic options [8][9][10]. Regardless of the host, CoNS might be generally prone to increased antimicrobial resistance carriage since CoNS isolated from various animal species also carried resistance to several classes of antimicrobials [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%